SOCIAL MEDIA PREFERENCE AMONG STUDENTS OF DELTA STATE UNIVERSITY AND DELTA STATE POLYTECHNIC OGWASHI-UKU - Lydia I UWAYAH (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This study examines social media preference among students of Delta State University, Abraka and Delta State Polytechnic Ogwashi-Uku. The study was backed up with uses and gratification theory. The study adopted survey method of ex-post- facto design. A sample size of 400 was drawn from the population. Multi-stage sampling technique was adopted, selecting undergraduate students from five faculties of Delta State University, Abraka and four from Delta Polytechnic Ogwashi–Uku. Questionnaire was used as the research instruments to collect data for the study. The researcher used descriptive statistics which comprises of simple percentage, mean and standard deviation using SPSS.  Findings from the study showed that facebook, whatsapp, and instagram were frequently used social media. Also, benefits derived from social media are information, fun and entertainment. Students between ages of 16-25 have the highest number for social media use. It also, showed that female students use facebook, snapchat and instagram frequently than the male students while male students frequently use twitter and linkedin.  And, technological exposure can influence social media preference. The study recommends that school management should provide informative, educative and entertaining online programmes more on social media for students to engage and improve their academics.